Elementary and Intermediate Algebra: Concepts & Applications (6th Edition)

Published by Pearson
ISBN 10: 0-32184-874-8
ISBN 13: 978-0-32184-874-1

Chapter 4 - Polynomials - 4.2 Negative Exponents and Scientific Notations - 4.2 Exercise Set: 6

Answer

Option (d)

Work Step by Step

RECALL: A negative exponent means reciprocal. Thus, $a^{-m} = \frac{1}{a^m}=(\frac{1}{a})^m$. Using the rule above gives: $(\frac{y^2}{x^3})^{-2}=(\frac{x^3}{y^2})^2$ Simplify using the rule $(a^m)^n=a^{mn}$ to obtain: $=\dfrac{x^{3(2)}}{y^{2(2)}} \\=\dfrac{x^6}{y^4}$ Thus, the answer is Option (d).
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.